The Scientific Value of Abstracts on Prostate Cancer Presented at the European Association of Urology Congresses - Ataei, Jasmin; Bach, Christian; Javan, Aida; Vögeli, Thomas-Alexander; Grafe, Christina; Rahnama'i, Mohammad Sajjad (Frontiers in Surgery, 2021)
Abstract Background: Scientific congresses are an important medium for presenting recent clinical findings. Wider dissemination of research requires publication. Objectives: To determine the publication rates of prostate cancer abstracts presented at the annual congress of the European Association of Urology (EAU). Design, Setting, and Participants: All abstracts with the term prostate cancer or carcinoma presented at the congress of the European Association of Urology from 2015 to 2018 were analyzed. We captured their publication rate, journal impact factor and time to publication. Moreover, we formulated a scoring system to determine the grade of discrepancy between the conclusions mentioned in the congress abstract and published abstract. Results: A total of 834 abstracts presented at EAU annual meeting included prostate cancer or carcinoma in their title. We recorded a publication rate of 56.8% with 474 of the 834 abstracts being published with a mean time of 12.5 months. Conclusion: Approximately, 57% of the prostate cancer abstracts presented at the EAU congress are published in peer reviewed journals. This acceptance rate indicates the high distribution and dissemination of these abstracts.